Lean manufacturing and firm performance: The incremental contribution of lean management accounting practices - Fullerton, Rosemary R.; Kennedy, Frances A.; Widener, Sally K. (Journal of Operations Management, 2014)
AbstractManufacturing firms operating in rapidly changing and highly competitive markets have embraced the continuous process improvement mindset. They have worked to improve quality, flexibility, and customer response time using the principles ofLean thinking. To reach its potential, lean must be adopted as a holistic business strategy, rather than an activity isolated in operations. The lean enterprise calls for the integration of lean practices across operations and other business functions. As a critical component for achieving financial control, management accounting practices (MAP) need to be adjusted to meet the demands and objectives of lean organizations. Our aim is to help both researchers and practitioners better understand how lean MAP can support operations personnel with their internal decision making, and operations executives and business leaders in their objective of increasing lean operations performance as part of a holistic lean enterprise strategy. We use survey data from 244 U.S. manufacturing firms to construct a structural equation model. We document that the extent of lean manufacturing implementation is associated with the use of lean MAP, and further that the lean MAP are related in a systematic way: simplified and strategically aligned MAP positively influences the use of value stream costing, which in turn positively influences the use of visual performance measures. We also find that the extent of lean manufacturing practices is directly related to operations performance. More importantly, lean manufacturing practices also indirectly affect operations performancethroughlean MAP. These findings are consistent with the notion that lean thinking is a holistic business strategy. In order to derive the greatest impact on performance, our results indicate that operations management cannot operate in a vacuum. Instead, operations and accounting personnel must partner with each other to ensure that lean MAP are strategically integrated into the lean culture. In sum, lean MAP provide essential financial control that integrates with and supports operations to achieve desired benefits.